The Representation of Complaints in English and Indonesian Discourses - Arafah, Burhanuddin; ., Kaharuddin (Opción, 2019)
This study compared the strategies of complaints presented by educated English native speakers and Indonesians via comparative quantitative research methods. The quantitative results showed that ENSs and INSs shared a similarity in the use of complaint strategies across the three offenses. In conclusion, the socio-cultural competence of the complaint strategies will not be used appropriately by non-native speakers of English and Indonesian without having an accurate knowledge in this area. Hence, language teachers should then be able to focus their instructions on the similarities and the differences between complaints in English and Indonesian.